2021
DOI: 10.2147/btt.s291768
|View full text |Cite
|
Sign up to set email alerts
|

Armored CAR T-Cells: The Next Chapter in T-Cell Cancer Immunotherapy

Abstract: Chimeric antigen receptor (CAR) T-cell therapy engineers T-cells to express a synthetic receptor which redirects effector function to the tumor, to improve efficacy and reduce toxicities associated with conventional treatments, such as radiotherapy and chemotherapy. This approach has proved effective in treating hematological malignancies; however, the same effects have not been observed in solid tumors. The immunosuppressive tumor microenvironment (TME) creates a significant barrier to solid tumor efficacy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 84 publications
1
42
0
Order By: Relevance
“…The next steps are to incorporate modifications that allow the adoptively transferred cells to persistent autonomously, maintain proliferative potential, outmaneuver the immunosuppressive tumor microenvironment, infiltrate tumor beds, and stimulate endogenous antitumor immunity. Each of these goals has been addressed extensively in preclinical T and NK cell studies [ 163 , 164 , 165 , 166 ], such as through the exogenous expression of IL-15, immune checkpoint inhibitors, chemokine receptors, or immunomodulatory proteins, but are usually targeted individually or in pairs due to the limited genetic pliability of mature immune cells. Stem cell engineering opens the door for increasingly complex designer cell products, and future research will need to reveal if the accumulated changes hinder immune cell antitumor efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The next steps are to incorporate modifications that allow the adoptively transferred cells to persistent autonomously, maintain proliferative potential, outmaneuver the immunosuppressive tumor microenvironment, infiltrate tumor beds, and stimulate endogenous antitumor immunity. Each of these goals has been addressed extensively in preclinical T and NK cell studies [ 163 , 164 , 165 , 166 ], such as through the exogenous expression of IL-15, immune checkpoint inhibitors, chemokine receptors, or immunomodulatory proteins, but are usually targeted individually or in pairs due to the limited genetic pliability of mature immune cells. Stem cell engineering opens the door for increasingly complex designer cell products, and future research will need to reveal if the accumulated changes hinder immune cell antitumor efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in solid tumors, the immunosuppressive tumor microenvironments (TME) represent a significant barrier that impairs the function of CAR T cells. Several approaches have been applied to alter the TME from immunosuppressive to pro-inflammatory, including the use of a conditioning regimen prior to T cell infusion, small molecules to interfere with immunosuppressive cells, and blocking antibodies such as anti-PD-1 scFv to inhibit immune checkpoints (142,143) as well as engineering CAR to express cytokine receptor or to secrete cytokines such as IL-12, IL-18, IL-15 to increase T cell persistence and anti-tumor efficacy (141,(144)(145)(146)(147). To date, the CAR T cell therapy for solid tumors in clinical trials has not been effective since T cells cannot penetrate and survive in the TME.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…These cytokines increase IFN-γ secretion, favouring T cell infiltration and persistence, as well as decrease the level of proangiogenic molecules, reactivating the endogenous immune system [ 132 ]. For CNS tumours, the local and the controlled administration of these immunomodulatory cytokines is paramount to minimise toxicities, since high toxicity has been related to their systemic application [ 133 ].…”
Section: Challenges and Opportunities Of Car T Cell Therapy In Paediatric Cns Tumoursmentioning
confidence: 99%
“…Although many preclinical studies have shown the feasibility of using TRUCKS, further research is warranted in paediatric CNS tumours. The selection of the appropriate interleukin(s) for each tumour type to produce a change in the immune state of the TME is essential to boost CAR T cell effector functions without increasing toxicities [ 123 , 133 ].…”
Section: Challenges and Opportunities Of Car T Cell Therapy In Paediatric Cns Tumoursmentioning
confidence: 99%